Math, asked by davkanika0824, 5 months ago

Plz tell the answer of the above question it's very urgent !!!!!​

Attachments:

Answers

Answered by Anonymous
2

Answer:

\implies - \dfrac{20}{27}

Step-by-step explanation:

\implies \sf \dfrac{x^2 - (x+2)(x+3)}{6x+1} = \dfrac{2}{3}

 \\

\implies \sf \dfrac{x^2 - (x+2) \times (x+3)}{6x+1} = \dfrac{2}{3} , \: x \neq - \dfrac{1}{6}

 \\

\implies \sf \dfrac{x^2 - (x^2 + 3x + 2x + 6)}{6x + 1} = \dfrac{2}{3}

 \\

\implies \sf \dfrac{x^2 - (x^2 + 5x + 6)}{6x+1} = \dfrac{2}{3}

 \\

\implies \sf \dfrac{x^2 - x^2 - 5x - 6}{6x+1} = \dfrac{2}{3}

 \\

\implies \sf \dfrac{-5x-6}{6x+1} = \dfrac{2}{3}

 \\

\implies \sf 3(-5x - 6) = 2(6x + 1)

 \\

\implies \sf -15x - 18 = 2(6x + 1)

 \\

\implies \sf -15x - 18 = 12x + 2

 \\

\implies \sf 15x - 12x = 2 + 18

 \\

\implies \sf 27x = 2 + 18

 \\

\implies \sf -27x = 20

 \\

\implies \sf x = - \dfrac{20}{27}, \: x \neq - \dfrac{1}{6}

 \\

\qquad \large{\underline{\boxed{\bf x = - \dfrac{20}{27}}}}

Similar questions